2010
DOI: 10.1007/s11738-010-0524-8
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic control of embryonic dormancy in apple seed: seven decades of research

Abstract: Embryonic dormancy is defined as a set of blocks imposed upon a process(es) cardinal for growth. In apple seeds, all these blocks are removed as a result of cold treatment (stratification), but some of them are also affected by light and/or hormonal treatments. This review summarizes published data related to the modes of action of above factors on the changes in the levels of endogenous hormones and some other plant growth regulators (e.g., hydrogen cyanide), and on certain enzymes involved in mobilization of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
56
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 56 publications
(60 citation statements)
references
References 134 publications
(131 reference statements)
2
56
1
Order By: Relevance
“…Embryos isolated from dormant apple seeds did not germinate or germinated very slowly, due to blockage of many physiological processes in the embryonic axes, and unbalanced plant phytohormone levels (Lewak 2011 and references therein). Dormancy of apple seeds may be overcome by cold stratification (Lewak 2011) or, in the case of isolated embryos, by application of various NO donors (Gniazdowska and others 2010b). We demonstrated that the most abundant PAs (Put and Spd) stimulated germination of dormant apple embryos similarly as it was described by Sińska and Lewandowska (1991).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Embryos isolated from dormant apple seeds did not germinate or germinated very slowly, due to blockage of many physiological processes in the embryonic axes, and unbalanced plant phytohormone levels (Lewak 2011 and references therein). Dormancy of apple seeds may be overcome by cold stratification (Lewak 2011) or, in the case of isolated embryos, by application of various NO donors (Gniazdowska and others 2010b). We demonstrated that the most abundant PAs (Put and Spd) stimulated germination of dormant apple embryos similarly as it was described by Sińska and Lewandowska (1991).…”
Section: Discussionmentioning
confidence: 99%
“…The role of ROS and RNS in regulation of seed germination is well described by the model of ''oxidative window'' or ''nitrosative door,'' respectively (Bailly and others 2008;. Under natural conditions dormancy of apple seeds is removed by 90-day-long cold (5°C) stratification (Lewak 2011). Such treatment leads to alterations in GAs, ABA, ethylene, and PA content (Lewak 2011 and references therein), which are accompanied by fluctuation in H 2 O 2 concentration in the tissue and NO production (Dębska and others 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Evident symptoms of apple embryos deep dormancy are: very slow and abnormal growth of seedlings. Morphological anomalies of water-grown dormant embryos are asynchronously developing cotyledons and shortened embryonic roots (Lewak 2011;Gniazdowska et al 2007Gniazdowska et al , 2010a. NO donors (e.g., SNP, SNAP, acidified NO 2 -) used for short term (signaling) treatment enhanced percentage of germinated embryos and stimulated growth of seedlings with both cotyledons equal in size and green (Table 1; Suppl.…”
Section: Discussionmentioning
confidence: 99%
“…Apple embryos are characterized by deep, embryonic dormancy, origin of which has been studied for many decades, and described in details by Lewak (2011). ROS and RNS were demonstrated as important players in the signaling pathways of hormones (ethylene, ABA) (Gniazdowska et al 2007(Gniazdowska et al , 2010a or plant growth regulators (polyamines) (Krasuska et al 2014a) involved in dormancy alleviation and germination of apple embryos.…”
Section: Introductionmentioning
confidence: 99%
“…20-25 C) or cold (e.g. 5 C) temperature) (Lewak 2011). During cold stratification of apple seeds (Malus domestica Borkh.)…”
Section: Introductionmentioning
confidence: 99%